Influence of leadership competencies on leaders' maturity in paddy farming technology in the Muda area, Malaysia - Masso, Wisam Yako Aziz (2017)
In developing countries such as Malaysia, rural people have depended on extension workers and farmers leaders for technical advice and information (Tiraieyari, 2009).The farmer leaders should influence others to adopt and practice the best technologies in their farming, so that they can improve their paddy productivity and increase their income. For these reasons, paddy farming leaders in study area play an important role in agricultural process and agricultural extension. The mature leader is the one who sees leadership as responsibility rather than privilege. They have integrity and consistency, they are usually modest, loosing no opportunity to stress that real achievement has come from team work and not from inspiration of just one individual (Wang et al., 2005). Hence, maturity is a combination of factors: attitude, skills, learning, education; but it is also a matter of values: honesty, respect, humbleness, loyalty. Usually, when a leader lacks of maturity, he / she creates and participates in fraudulent or illegal situations that affect the followrs (Goleman, 1998). The best leaders are those who can contribute and achieve the goals, when a leader achieves goals, it may be assumed that he has an acceptable level of maturity (Balsanelli et al., 2008). However, paddy farming leaders in the granary area are facing some problems. Among those is the adoption of the technology that has been transferred to them, about which they are not very knowledgeable. Their knowledge and skills are low because of the lack of training offered to them from agencies, resulting in a lack of competences (Ahmad et al., 2015). Therefore, they do not transfer new information that they have about new technology to other farmers because the relation or the communication between the leaders and farmers is not well conducted. As a result, their maturity level may be regarded as low.